Mucopolysaccharidoses and Orthopedic Management (Focused also on Craniocervical Junction) - Lampe, Christina; Lampe, Christian Gerhard (Journal of Child Science, 2018)
Mucopolysaccharidoses (MPSs) are multisystemic, chronic progressive, heterogeneous, and life-threatening diseases, involving severely the musculoskeletal system, in particular in MPS I, II, IV, VI, VII, and less prevalent in MPS III. Accumulation of glycosaminoglycans (GAGs) in soft tissues, such as ligaments, tendons, and joint capsules, as well as in cartilage, and bone lead to orthopedic complications: joint stiffness, contractures, and skeletal deformities, resulting in hip dysplasia, genua valga, feet deformities, kyphoscoliosis, narrowing of the spinal canal, atlantoaxial instability, carpal tunnel syndrome, trigger finger, and growth retardation. These complications significantly reduce the quality of life due to impaired mobility, loss of independency, and pain. Compression of the cervical spinal cord is also life threatening. According to the progressive nature of MPSs, musculoskeletal symptoms worsen over time and surgical intervention may be inevitable. However, due to the increased anesthesia risk of MPSs, surgical intervention has to be evaluated carefully by a multidisciplinary team. Additionally, due to the rarity of the diseases, not many standards or recommendations are available to determine the indication of a surgical intervention, so each intervention must be decided individually, based on the few data available. In addition, conservative treatment should be taken into consideration. Physiotherapy, pain medication, insoles, orthosis, braces, corsets, and special footwear play a pivotal role. Unfortunately, the skeletal tissues are poorly vascularized and enzyme replacement therapy does not have much effect on them. It is important to detect and observe musculoskeletal complications in the regular follow-up visits, in particular the life-threatening compression of the cervical spinal cord.
Keywords: musculoskeletal; joints; craniocervical junction; mucopolysaccharidoses; dysostosis multiplex